Pericytes modulate endothelial inflammatory response during bacterial infection - Thaynara Parente de Carvalho (2023)
Pericytes are pluripotent mesenchymal cells located around blood vessels. There is evidence that the pericyte plays a significant role in the development of metabolic and infectious diseases, including cytomegalovirus and Bartonella henselae infections. Taking into account the importance of these cells and a lack of previous studies on the role of pericytes during bacterial infections, the goal of this study was to investigate the interaction and function of the pericytes in infections caused by intracellular bacteria, including Brucella ovis and Listeria monocytogenes, and the direct effect of the pericyte on endothelial cells. This study described the role of the pericyte during bacterial infection in vitro and in vivo. Inoculation of cultured pericytes with B. ovis and L. monocytogenes demonstrated that pericytes are not permissive to intracellular bacterial infections. Co-cultured endothelial cells and pericytes (2:1 respectively) or endothelium alone were inoculated with B. ovis or L. monocytogenes, or stimulated with LPS at a low concentration. Under those conditions the presence of pericytes decreased and expression of adhesion molecules (PECAM-1 and ICAM-1) and pro-inflammatory molecules (CCL-2 and IL-6). The presence of fibrinous peritonitis was observed in a murine model with depletion of pericytes infected with L. monocytogenes and B. ovis via the intraperitoneal route, whereas none of non-depleted control mice developed peritonitis under the same experimental conditions. Depleted mice had increased levels of CCL-2 in the serum. In addition, we measure the levels of connexins expressed in our co-culture, and the one with more expression between the endothelial cells and pericytes was connexin-43. To investigate how endothelial cells and pericytes communicate, we blocked connexin 43 using a chemical inhibitor (GAP19) or silence Connexin-43 expression using siRNA. Innibition of connexin-43 function led to an increase in expression of adhesion and pro-inflammatory molecules, demonstrating the function of connexin-43. Mice treated with GAP19 in vivo and infected with B. ovis had increased bacterial loads in the liver and spleen, and elevated CCL-2 levels in their sera. All results demonstrate that pericytes modulate the inflammatory response of endothelial cells to bacterial stimuli.